GRAPHIC AND ORTHOGRAPHIC FEATURES OF ENGLISH AND GEORGIAN-LANGUAGE INTERNET DISCOURSE (BASED ON YOUTUBE VIDEO COMMENTS) - Akhvlediani, Ana (International Journal of Innovative Technologies in Social Science, 2023)
The present paper is devoted to the investigation of the linguistic (mainly graphic and orthographic) features of Internet Discourse, as a new type of language. Graphic and orthographic features of Internet Discourse are investigated on the basis of English and Georgian YouTube video comments. The analysis showed that Internet Discourse is characterized by specific graphic and orthographic features: the usage of emoticons, unusual usage of punctuation marks, multiple punctuation, unconventional spelling, capitalization, etc.